Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Viral Load in the Upper Respiratory Tract of Children and Adults With Early Acute Coronavirus Disease 2019 (COVID-19). (6th August 2020) - Baggio, Stéphanie; L'Huillier, Arnaud G; Yerly, Sabine; Bellon, Mathilde; Wagner, Noémie; Rohr, Marie; Huttner, Angela; Blanchard-Rohner, Géraldine; Loevy, Natasha; Kaiser, Laurent; Jacquerioz, Frédérique; Eckerle, Isabella
Abstract: The factors that contribute to transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) by children are unclear. We analyzed viral load at the time of diagnosis in 53 children and 352 adults with coronavirus disease 2019 (COVID-19) in the first 5 days post symptom onset. No significant differences in SARS-CoV-2 RNA loads were seen between children and adults.